Improving Indonesian History Learning Outcomes by Applying the Think Pair And Share Model - Anilawa Anilawa (Pinisi Journal of Education and Management, 2023)
The cooperative learning model of the Think Pair and Share (TPS) type is a "cooperative learning model that was first developed by Professor Frank Lyman and his colleagues at the University of Maryland in 1981. This research is a class action research. The research subjects were students of class X OTKP 4 SMK Negeri 2 Palu, a total of 18 people. While the research procedure consists of 4 stages, namely: planning, implementation, observation and reflection. Furthermore, data analysis was carried out through three stages, namely data reduction, data presentation, and data/conclusion verification. The results showed that the Think Pair and Share Model can improve learning outcomes. The Think Pair and Share Model can improve Indonesian History learning outcomes in class X OTKP 4 SMK Negeri 2 Palu, even semester of the 2021/2022 academic year.